Kaji Sistem Peralatan Penyerap Kalor pada Kotak Penyimpan Darah - Dogar Situmeang; Ahmad Syuhada (Jurnal Teknik Mesin Unsyiah, 2013)
This research aims to produce an effective heat sink with thermoelectric which is a semi conductor devices having several pairs of type P (positive) and N (negative) S content. Type P has a lower energy level while type N had a higher energy level. This tool, equipped with a heat sink as the heater, is mounted on a chamber to create a heat exchanger for a portable cooler box. Three types of thermoelectric modules were used with different fin types to find out the their effects on the temperature, T, and the rate of heat transfer, Q, inside the cooler box. The results shows that with the blood volume of 250 cc, the blood temperature can be decreased from 29 oC to 5.8 oC within 145 minutes. The ideal temperature for the blood storage ranges from 1 oC to 6 oC. Among the three types of fins that were tested, the most effective heat transfer was given by fin type no. 3, the cylindrical-shaped fins. The heat transfer obtained is 12.83 W/m2 oC. The lowest heat transfer was given by fin type no. 2, which is a slot type, with heat transfer rate of 3.85 W/m2 oC.